The hyaluronan-related genes HAS2, HYAL1-4, PH20 and HYALP1 are associated with prognosis, cell viability and spheroid formation capacity in ovarian cancer - Jette Riecks; Arianna Parnigoni; Balázs Győrffy; Ludwig Kiesel; Alberto Passi; Davide Vigetti; Martin Götte (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose Hyaluronan modulates tumour progression, including cell adhesion, cohesion, proliferation and invasion, and the cancer stem cell phenotype. In ovarian cancer, high levels of stromal hyaluronan are associated with poor prognosis. In this work, hyaluronan synthases (HAS1-3) and hyaluronidases (HYAL1-4, PH-20, HYALP1) were examined with regard to different levels of gene expression and its influence on ovarian cancer patients’ survival. The impact of a siRNA depletion of HAS2 was investigated in vitro. Methods Using the Kaplan–Meier Plotter tool, we investigated the influence of hyaluronic synthases and hyaluronidases on the survival of a collective of 1435 ovarian cancer patients. Differences in gene expression between normal (n = 46) and cancerous (n = 744) ovarian tissue were examined using the TNMplot database. Following an evaluation of hyaluronan-related gene expression in the ATCC ovarian cancer panel, we studied SKOV3 and SW 626 ovarian cancer cells subjected to HAS2 siRNA or control siRNA treatment in terms of HAS1-3, HYAL2 and HYAL3 mRNA expression. We investigated the ability to form spheroids using the Hanging Drop method and the response to chemotherapy at different concentrations using the MTT Assay. By STRING analysis, interactions within the enzymes of the hyaluronic acid system and with binding partners were visualized. Results HAS1, HYAL1 and HYAL4 mRNA expression is significantly upregulated, whereas HAS2, HYAL2 and HYAL3 mRNA expression is significantly downregulated in ovarian cancer tissue compared to controls. HAS2 improves cell viability, the capability to form tumour spheroids and has a negative prognostic value regarding overall survival. Lower HAS2 expression and high expression of HYAL2 and HYAL3 favours the survival of ovarian cancer patients. HAS2 knockdown cells and control cells showed a moderate response to combinatorial in vitro chemotherapy with taxol and cisplatin. Conclusion In conclusion, our study shows that the hyaluronic acid system has a relevant influence on the survival of ovarian cancer patients and could therefore be considered as a possible prognostic factor.